APATISME POLITIK PEMILIH PEMULA DAN PAPARAN DRAMA KASUS KORUPSI DI LAYAR KACA - Asmaul Husna (SOURCE : Jurnal Ilmu Komunikasi, 2018)
Implementation of periodically election periodically show that Indonesia is one of the countries which embrace democratic system. Meanwhile in the process, election requires political participation presences from citizen to declare and define their desire as a source of the legitimacy. However the facts, political participation of the citizen in 2017’s election tend to decrease than a couple years before. This matter occur because amount of corruption news that to be exposed in mass media. It was impact to disappearance of political trust and interest the beginner voters who didn’t realize that their apathetic attitude would aggravate to political environtment in Indonesia. This research aim to analysis how the corruption news which reported in mass media take effect about the apathetic attitude of beginner voters. Which uses cultivation theory, this research apply the quantitative approach and positivism paradigm that use survey research. Data collection techniques of probability sampling with 93 respondents samples. With simple linear regression method, was indicate a positive and significant dominant influence about the media access experience of beginner voters with political apathetic tendency, with contribution of influence 73,1%, R 2=0.0731, ß=0,855 and p<0,01. Keywords: Beginner Voters, Corruption, Media Effect, Political Apathetic.